Nanocrystal–Dye Interactions: Studying the Feasibility of Co‐Sensitization of Dyes with Semiconductor Nanocrystals. Issue 18 (22nd August 2017) - Mittal, Mona; Sapra, Sameer
Abstract: One of the recent developments in enhancing the performance of quantum dot sensitized solar cells (QDSSCs) is to combine QDs with dyes in order to overcome the drawbacks of QDSSCs. However, implementation of this requires a detailed investigation of the interaction between QDs and dye. Here, we have studied the effect of size and surface ligands in the interaction of CdSe nanocrystals (NCs) with Ru N‐719 dye. The interaction mechanism is investigated by steady‐state and time‐resolved photoluminescence spectroscopy, indicating the involvement of apparent static as well as dynamic quenching. Further analysis of dynamic quenching reveals the contribution of Förster resonance energy transfer and electron transfer from NCs to the dye. The Marcus model of electron transfer rationalizes the random trends of experimental electron transfer rates, which depend on the energetic offsets between the two species and the reorganizational energy. For understanding the kinetics of energy/charge transfer from CdSe NCs to Ru N‐719 dye, a Poisson binding model has been proposed that assumes a Poisson distribution of dye molecules around CdSe NCs. The variation of quenching rate constants and PL quenching rate both follow the same trend, supporting the main contribution of kinetics in the interaction of CdSe NCs with the dye. Abstract : Size matters ! The rate of energy transfer, k FRET, decreases with increase in the size of CdSe NCs owing to a decrease in the spectral overlap integral, J . The random trends of electron transfer rates, k eT have been explained by the Marcus model of electron transfer, where the free energy and the reorganizational energy compete with each other. The Poisson binding model has also been used to calculate the average number of Ru dye molecules, m q, bound to each NC.